NUCLEATION MECHANISM OF STRAIN-INDUCED INASSBP QUANTUM DOTS AND PITS AT LIQUID PHASE EPITAXY ON InAs (100) SUBSTRATE - V. M. Aroutiounian; K. M. Gambaryan; N. G. Alaverdyan; A. K. Simonyan
Application of the InAsSbP and other similar quaternary materials open up interesting physical and technological prospects for the controlled growth of QDs, QPs and dots–pits cooperative systems. At the growth of lattice matched with the substrate heterolayers from the quaternary liquid phase, corresponding variation of the third and fourth components allows providing needed sign of the misfit, i.e. to provide tensile or compressive misfit stress.
Keywords: Physics; Electronic structure and electrical properties of surfaces